H Protein of Bacteriophage 16-3 and RkpM Protein of Sinorhizobium meliloti 41 Are Involved in Phage Adsorption - Putnoky, Péter (American Society for Microbiology, 2004)
The strain-specific capsular polysaccharide KR5 antigen of Sinorhizobium meliloti 41 is required both for invasion of the symbiotic nodule and for the adsorption of bacteriophage 16-3. In order to know more about the genes involved in these events, bacterial mutants carrying an altered phage receptor were identified by using host range phage mutants. A representative mutation was localized in the rkpM gene by complementation and DNA sequence analysis. A host range phage mutant isolated on these phage-resistant bacteria was used to identify the h gene, which is likely to encode the tail fiber protein of phage 16-3. The nucleotide sequences of the h gene as well as a host range mutant allele were also established. In both the bacterial and phage mutant alleles, a missense mutation was found, indicating a direct contact between the RkpM and H proteins in the course of phage adsorption. Some mutations could not be localized in these genes, suggesting that additional components are also important for bacteriophage receptor recognition.